Technopreneurs Millennial in Indonesia: The Acquisition and Application Knowledge - Ardianus Laurens Paulus (International Journal of Business Economics (IJBE), 2021)
The development of technical knowledge has encouraged many business activities utilizing communication tools and technologies in business processes. This study aims to test the effect of knowledge acquisition and knowledge application of millennial technopreneurs in Indonesia in utilizing technology for their business activities. A total of 153 respondents were surveyed through online questionnaires. SEM analysis is used to test the research model. This study found that millennial technopreneurs ignore acquiring knowledge about business activities. But significant results showed that millennial technopreneurs immediately applied knowledge without looking at previous knowledge acquisition processes.